2008
DOI: 10.1194/jlr.m800024-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein enhances macrophage lipoprotein lipase expression

Abstract: High serum levels of C-reactive protein (CRP), a strong predictor of cardiovascular events, are documented in patients with type 2 diabetes. Accumulating evidence suggests that CRP could directly promote arterial damage. To determine the role of CRP in diabetic atherosclerosis, we examined the effect of CRP on the expression of macrophage lipoprotein lipase (LPL), a proatherogenic molecule upregulated in type 2 diabetes. Treatment of human macrophages with native CRP increased, in a dose-and timedependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Thus, it was Fc g RII rather than Fc g RI that was involved in the sLOX-1 release from activated macrophages induced by CRP. Our results agreed with previous fi ndings that CRP enhanced macrophage lipoprotein lipase expression through CD32 rather than CD64 ( 44 ). Moreover, ROS production, TACE activation, and phosphorylation of p47 phox induced by CRP were all attenuated by pretreatment with antibody to CD32 or with CD32 siRNA.…”
Section: Crp Regulated Slox-1 Release From Macrophages Derived From Psupporting
confidence: 82%
“…Thus, it was Fc g RII rather than Fc g RI that was involved in the sLOX-1 release from activated macrophages induced by CRP. Our results agreed with previous fi ndings that CRP enhanced macrophage lipoprotein lipase expression through CD32 rather than CD64 ( 44 ). Moreover, ROS production, TACE activation, and phosphorylation of p47 phox induced by CRP were all attenuated by pretreatment with antibody to CD32 or with CD32 siRNA.…”
Section: Crp Regulated Slox-1 Release From Macrophages Derived From Psupporting
confidence: 82%
“…Different studies have shown controversial results according to the effect of CRP on the expression and activity of the enzymes. 30,26,38,39 In this study, the lack of association between hs-CRP and the lipolytic enzymes should not exclude more complex inflammatory mechanisms in the regulation of enzyme activity.…”
Section: Discussionmentioning
confidence: 77%
“…Both glucocorticoids and insulin are essential for LPL translation and transmembrane transport [68]. Creactive protein (CRP) also increases macrophage LPL expression and secretion at the posttranscriptional level [69].…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%